9th Research in Engineering Education Symposium (REES 2021) and 32nd Australasian Association for Engineering Education Confere 2022
DOI: 10.52202/066488-0071
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Engineering Education: Preliminary Results from a Scoping Review

Abstract: There is today a broad consensus that emotions influence all forms of teaching and learning, and scholarship on Emotions in Engineering Education (EEE) is an emerging and rapidly growing field. However, this nascent research is currently very dispersed and not well consolidated. There is also a lack of knowledge about the state of the art, strengths, and limitations of the existing literature in the field, gaps, and future avenues for research. PURPOSEWe have conducted a scoping review of EEE research, aiming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 13 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…Second, the affective indications in our findings, coupled with studies such as Walther et al's (2011) work on accidental competencies and Lönngren's work on emotion (e.g., Lönngren, Adawi, & Berge, 2021; Lönngren, Bellocchi, et al, 2021), point to the need for further research on how affective factors impact students' preparation for and transition to work. What factors support or hinder participants' ability to apply existing skills to new contexts, or to learn new skills at work?…”
Section: Discussionsupporting
confidence: 53%
“…Second, the affective indications in our findings, coupled with studies such as Walther et al's (2011) work on accidental competencies and Lönngren's work on emotion (e.g., Lönngren, Adawi, & Berge, 2021; Lönngren, Bellocchi, et al, 2021), point to the need for further research on how affective factors impact students' preparation for and transition to work. What factors support or hinder participants' ability to apply existing skills to new contexts, or to learn new skills at work?…”
Section: Discussionsupporting
confidence: 53%
“…This study differs from previous work on affect and emotions in engineering in several ways: a recent scoping review (Lönngren, Bellocchi, et al, 2021) found that only 10% of papers about emotions in engineering education related to the concept of achievement emotions (which are one aspect of epistemic affect, as described previously), whereas there is a larger focus on topics such as emotional intelligence (a keyword for 46 of the 184 papers in the review) (e.g., Adams et al, 2011;Roeser, 2012). We are in a smaller subset of researchers studying the intertwined nature of affect in the doing of engineering (epistemic affect), rather than merely as something required to interact between people or their attitudes/global affect.…”
Section: Major Findingsmentioning
confidence: 79%
“…6.1.1 | RQ1: Uncertainty and complexity in the problem cause strong emotions Emotion has been described as a "rapidly expanding, but internationally dispersed field" of study in engineering education (p. 232), most often introduced to complement or inform other areas of educational research, which has significant areas remaining to be explored (Lönngren, Bellocchi, et al, 2021). The range of both positive and negative emotions identified in this study through affective expressions is similar to the range of emotions reported in the literature elsewhere: first-year engineering students completing tool-based cutting challenges also reported feeling anxiety, frustration, stress, calm, comfort, and interest (Hu et al, 2016).…”
Section: Major Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although engineering ethics remains very rationality‐oriented, there is a growing interest in emotion in engineering education (Lönngren et al, 2023; Lönngren, Bellocchi, et al, 2021; Villanueva et al, 2018) and this is reflected in a growing literature on emotions in engineering ethics education also. Examples include Pantazidou and Nair (1999) and Riley et al (2009) who have argued for engineering design to be reframed through an ethics of care perspective.…”
Section: Introductionmentioning
confidence: 99%